2008
DOI: 10.1093/rheumatology/kem287
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI in NPSLE patients reveals increased parietal and frontal brain activation during a working memory task compared with controls

Abstract: NPSLE patients showed greater frontoparietal activation than the other groups during the memory task, suggesting a greater need to recruit extra cortical pathways, possibly to supplement impaired function of standard pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 15 publications
2
48
0
1
Order By: Relevance
“…Two fMRI studies previously reported increased regional activation patterns in patients with NPSLE in response to memory and simple motor tasks compared with healthy controls (25,26). Another fMRI study of 10 pediatric SLE patients, not selected for NPSLE, also reported increased cortical activation patterns compared with healthy controls in response to memory, attention and The coordinates and cluster sizes of the regions with significant differences in BOLD signal intensity between the ST and LT subjects during performance of the modified Sternberg task (two shapes retention phase) are listed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two fMRI studies previously reported increased regional activation patterns in patients with NPSLE in response to memory and simple motor tasks compared with healthy controls (25,26). Another fMRI study of 10 pediatric SLE patients, not selected for NPSLE, also reported increased cortical activation patterns compared with healthy controls in response to memory, attention and The coordinates and cluster sizes of the regions with significant differences in BOLD signal intensity between the ST and LT subjects during performance of the modified Sternberg task (two shapes retention phase) are listed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fMRI provides an objective measure of functional neural networks solicited by specific probes. Three previous fMRI studies in SLE patients compared with healthy controls have all demonstrated abnormally increased regional brain activation patterns in areas targeted by specific tasks (24)(25)(26). We asked whether these abnormalities also correlate with disease duration.…”
Section: Differences In Regional Brain Activation Patterns Assessed Bmentioning
confidence: 95%
“…Evidence supports the notion that increased effort of a task results in enhanced activation on fMRI. [61][62][63] Fitzgibbon et al 64 also examined working memory, executive function and attention in adult SLE patients and also found greater frontoparietal activation in adult SLE patients than healthy controls, implying also that the same cognitive operations required more cortical activity in SLE patients.…”
Section: Association Of Regional Brain Activity and Domains Of Neurocmentioning
confidence: 99%
“…En pacientes con LESNP se encontró una baja perfusión en el lóbulo frontal al utilizar SPECT y la intensidad de esta lesión se correlacionó con mayor déficit cognitivo 67 . En lo que respecta a la RNM funcional se ha observado una mayor activación frontoparietal en tareas de memoria, posiblemente por reclutar más vías neuronales por defecto de las originales 68 , y alteraciones en la sustancia blanca del cuerpo calloso en pacientes LESNP 69,70 o un adelgazamiento de la sustancia gris cortical y subcortical 71,72 . No se encontró asociación en la disfunción endotelial cerebral cuantificada a través de Eco Doppler 22,73 , ni en histograma de transferencia magnética 74 .…”
Section: Imágenes Diagnósticasunclassified